IF HIGHER EDUCATION IS A RIGHT, AND DISTANCE EDUCATION IS THE ANSWER, THEN WHO WILL PAY? - Meyer, Katrina A. (Online Learning, 2008)
If higher education is a right, and distance education is the avenue for making higher education universally available, then who shall pay? This article asks (1) can state governments in the United States afford to fund this initiative and (2) can public higher education institutions in the U.S. fund this effort through capitalizing on cost-efficiencies of online learning? To answer the first question, data on funding of higher education by states are reviewed and a negative conclusion reached. To answer the second question, research on methods for achieving cost-efficiencies through online learning is reviewed and a cautious positive conclusion is reached, assuming states and institutions are willing to invest in the people and processes, and the time, effort, and will that make achieving efficiencies possible.